DNA methylation as a tool to explore ageing in wild roe deer populations. (30th October 2021) - Lemaître, Jean‐François; Rey, Benjamin; Gaillard, Jean‐Michel; Régis, Corinne; Gilot‐Fromont, Emmanuelle; Débias, François; Duhayer, Jeanne; Pardonnet, Sylvia; Pellerin, Maryline; Haghani, Amin; Zoller, Joseph A.; Li, Caesar Z.; et al.
Abstract: DNA methylation‐based biomarkers of ageing (epigenetic clocks) promise to lead to new insights into evolutionary biology of ageing. Relatively little is known about how the natural environment affects epigenetic ageing effects in wild species. In this study, we took advantage of a unique long‐term (>40 years) longitudinal monitoring of individual roe deer ( Capreolus capreolus ) living in two wild populations (Chizé and Trois‐Fontaines, France) facing different ecological contexts, to investigate the relationship between chronological age and levels of DNA methylation (DNAm). We generated novel DNA methylation data from n  = 94 blood samples, from which we extracted leucocyte DNA, using a custom methylation array (HorvathMammalMethylChip40). We present three DNA methylation‐based estimators of age (DNAm or epigenetic age), which were trained in males, females, and both sexes combined. We investigated how sex differences influenced the relationship between DNAm age and chronological age using sex‐specific epigenetic clocks. Our results highlight that old females may display a lower degree of biological ageing than males. Further, we identify the main sites of epigenetic alteration that have distinct ageing patterns between the two sexes. These findings open the door to promising avenues of research at the crossroads of evolutionary biology and biogerontology.